2002
DOI: 10.1007/s00417-002-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide/guanylate cyclase pathways and flow in anterior segment perfusion

Abstract: Under organ culture perfusion conditions, modulation of the nitric oxide/guanylate cyclase system alters the flow rate through the trabecular meshwork within a total range of 20%; i.e. the difference between inhibition of NO synthesis and the presence of a NO-donor. These results indicate that the nitric oxide/guanylate cyclase system plays a role in aqueous humour dynamics and, therefore, in the regulation of intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 13 publications
4
60
0
Order By: Relevance
“…Small increases in OF are produced by modulation of the nitric oxide system in organ-cultured human anterior segments. 25 Nitric oxide decreases cell volume in the trabecular meshwork and increases OF in porcine eye anterior segments, suggesting that the nitric oxide-induced alterations in cell volume may regulate outflow resistance. 26 IOP and AHF are decreased in isolated pig eyes perfused with nitrovasodilators, 27 suggesting mechanisms independent of ocular vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Small increases in OF are produced by modulation of the nitric oxide system in organ-cultured human anterior segments. 25 Nitric oxide decreases cell volume in the trabecular meshwork and increases OF in porcine eye anterior segments, suggesting that the nitric oxide-induced alterations in cell volume may regulate outflow resistance. 26 IOP and AHF are decreased in isolated pig eyes perfused with nitrovasodilators, 27 suggesting mechanisms independent of ocular vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…16 The NO-donating compounds effectively decrease conventional outflow resistance, leading to a decrease in IOP and outflow rate in different animal models, including rabbits, 21-24 pigs, 25 dogs, 22 and monkeys, 22,26 and in perfused postmortem human eyes. 27,28 Our previous study 29 further showed that eNOS/NO is a key regulator of outflow facility and …”
mentioning
confidence: 99%
“…4 An excess of NO, produced by inducible nitric oxide synthases (iNOS) upon stimulation, is thought to cause cell injury by nitrosative stress and this may occur in certain diseases. In the eye, NO contributes to allergic conjunctivitis, 5 glaucoma, 6 diabetic retinopathy, 7 and also cataract. 8,9 OH·, another highly reactive free radical has been shown to contribute to lens crystalline modification.…”
Section: Discussionmentioning
confidence: 99%